2010
DOI: 10.1074/jbc.m110.101592
|View full text |Cite
|
Sign up to set email alerts
|

Extended N-Sulfated Domains Reside at the Nonreducing End of Heparan Sulfate Chains

Abstract: Heparan sulfate (HS) serves as a cell-surface co-receptor for growth factors, morphogens, and chemokines. These HS and protein binding events depend on the fine structure and distribution of domains along an HS chain. A given domain can vary in terms of uronic acid epimer, N-and O-sulfate, and N-acetate content. The most highly sulfated regions of HS chains, N-sulfated (NS) domains, play prominent roles in HS and protein binding. We have analyzed HS oligosaccharides from various mammalian sources and provide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 48 publications
7
54
0
Order By: Relevance
“…The highly sulfated domain, also known as the S-domain, contributes to the binding to growth factors and chemokines. This domain contains the disaccharide repeating units -IdoUAϮ2S-GlcNS6S-and -GlcUA-GlcNS6S- (24). Although the IdoUAϮ2S-GlcNS6S linkage is known to be resistant to heparanase action, the reason for the lack of cleavage of the GlcUA-GlcNS6S linkage in the S-domain is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The highly sulfated domain, also known as the S-domain, contributes to the binding to growth factors and chemokines. This domain contains the disaccharide repeating units -IdoUAϮ2S-GlcNS6S-and -GlcUA-GlcNS6S- (24). Although the IdoUAϮ2S-GlcNS6S linkage is known to be resistant to heparanase action, the reason for the lack of cleavage of the GlcUA-GlcNS6S linkage in the S-domain is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact the modification of NDST-1 is exclusively toward the reducing end, our model suggests that the cluster of N-S domain should be longer if the N-sulfation is initiated at the nonreducing end. Indeed, structural analysis of the HS from various tissues indicated that the size of N-S domain is longer than those N-S domains identified in the middle of polysaccharide (28). NDST-1 contains both N-deacetylase and N-sulfotransferase domains.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Briefly, GAGs were released using 0.5 M NaOH, followed by purification using weak anion exchange chromatography. Samples were then digested into disaccharides by heparin lyases I, II, and III from Flavobacterium heparinum (Ibex, Montreal, Canada) at 37°C.…”
Section: Hs Disaccharide Analysismentioning
confidence: 99%